Using unmanned aerial vehicles to estimate body volume at scale for ecological monitoring - Thomas C. Stone; Katrina J. Davis (Methods in Ecology and Evolution)
Abstract Demographic data are essential to construct mechanistic models to understand how populations change over time and in response to global threats like climate change. Existing demographic data are either lacking or insufficient for many species, particularly those that are challenging to obtain direct measurements from that can be used to estimate demographic rates, like marine mammals. A method for collecting accurate demographic data to construct robust demographic models at scale would fill this knowledge gap for difficult‐to‐access species. We introduce a novel, non‐invasive method to estimate the 3D body size (volume) of pinnipeds (seals, sea lions and walruses) that will allow monitoring at high spatial and temporal scales. Our method integrates 3D structure‐from‐motion photogrammetry data collected via planned flight missions using off‐the‐shelf, multirotor unmanned aerial vehicles (UAVs). We apply and validate this method on the grey seal Halichoerus grypus, a pinniped species that spends much of its time at sea but is predictably observable during its annual breeding season. We investigate the optimal ground sampling distance (GSD) for surveys by calculating the success rates and accuracy of volume estimates of individuals at different altitudes. Based on current technology, we establish an optimal GSD of at least 0.8 cm px−1 for animals similar in size to UK grey seals (~1.2–2.5 m length), making our method reproducible and applicable to other species. We found volume estimates were accurate and could be successfully estimated for up to 68% of hauled‐out seals in study areas. Our method accurately estimates individual body volume of pinnipeds in a time‐ and cost‐effective manner while minimising disturbance. While the approach is applied to pinnipeds here, the method could be adapted to further taxa that are otherwise challenging to obtain direct measurements from. Our proposed approach therefore has the potential to fill demographic research gaps, which will improve our ability to protect and conserve species into the future.